2011
DOI: 10.1371/journal.pone.0017301
|View full text |Cite
|
Sign up to set email alerts
|

Polysaccharides Isolated from Açaí Fruit Induce Innate Immune Responses

Abstract: The Açaí (Acai) fruit is a popular nutritional supplement that purportedly enhances immune system function. These anecdotal claims are supported by limited studies describing immune responses to the Acai polyphenol fraction. Previously, we characterized γδ T cell responses to both polyphenol and polysaccharide fractions from several plant-derived nutritional supplements. Similar polyphenol and polysaccharide fractions are found in Acai fruit. Thus, we hypothesized that one or both of these fractions could acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
65
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(73 citation statements)
references
References 85 publications
4
65
0
4
Order By: Relevance
“…cd T cells seem particularly responsive to certain nutrient properties found in various food and supplement products, especially those with high antioxidant values (Table 4). 69,[118][119][120][121][122][123][124][125][126][127] In a double-blind placebocontrolled randomized control trial, capsules containing fruit and vegetable concentrate (containing, among other compounds, standardized levels of b-carotene, vitamin C, vitamin E, folate and calcium) were given to law school students, taken as a representative of young adults living with modern day stresses, over a period of 11 weeks. 128 cd T cells were found to be specifically increased (by about 30%; no change in circulating ab T cells) in parallel to an increase in the antioxidant capacity of the study subjects, and in vitro analyses showed that this effect was associated with a more tempered inflammatory response upon phorbal myristate acetate stimulation.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
See 2 more Smart Citations
“…cd T cells seem particularly responsive to certain nutrient properties found in various food and supplement products, especially those with high antioxidant values (Table 4). 69,[118][119][120][121][122][123][124][125][126][127] In a double-blind placebocontrolled randomized control trial, capsules containing fruit and vegetable concentrate (containing, among other compounds, standardized levels of b-carotene, vitamin C, vitamin E, folate and calcium) were given to law school students, taken as a representative of young adults living with modern day stresses, over a period of 11 weeks. 128 cd T cells were found to be specifically increased (by about 30%; no change in circulating ab T cells) in parallel to an increase in the antioxidant capacity of the study subjects, and in vitro analyses showed that this effect was associated with a more tempered inflammatory response upon phorbal myristate acetate stimulation.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
“…For example, treating renal carcinoma cells subjected to oxidative stress with the strong antioxidant, N-acetylcysteine, blunted the inflammatory response and activation of Vc9Vd2 T cells by downregulating the ectopic expression of the stress-induced molecule, MSH2. 79 Therefore, some of these immunomodulatory bioactive compounds, which include diverse items like procyanidins from unripe apple peels 129 and polysaccharide components of the Acai berry, 119 their noted influence on cd T cells may be through the modulation of the type of stress signals displayed by cells that mobilize their activity. In contrast, other compounds, such as the aforementioned alkylamines (e.g.…”
Section: Defined By Experiences Tainted By Innate Tendenciesmentioning
confidence: 99%
See 1 more Smart Citation
“…increased longevity in flies submitted to a high Saturated Fatty Acid (SFA) diet or deficient in enzymatic anti-oxidants such Superoxide Dismutase 1 (SOD1); dermatological care against disorders such as psoriasis, atopic dermatitis; cosmetic care); [15][16][17][18][19] (vi) Infections (e.g. through stimulation of innate immune response); 29,30 (vii) Pain (e.g. reduction of C-Reactive Protein (C-RP) in humans, albeit not statistical significant);…”
Section: Health Benefits Of the Açai Fruit Preventive And Therapeuticmentioning
confidence: 99%
“…Further sugars, such as rhamnose, fucose, and mannose, occur to a lesser extent. Different AG preparations are already in use in several traditional and natural medical products worldwide and are subject to studies due to their immune-modulating properties (15)(16)(17).…”
mentioning
confidence: 99%